سیاسات المکتبة المتعلقة باستخدام شبکات التواصل الاجتماعى فى المکتبات الأجنبیة :دراسة تحلیلیة مع استنباط سیاسة للمکتبات العربیة - د. غدیر مجدى عبد الوهاب (المجلة الدولية لعلوم المكتبات والمعلومات)
The massive developments of ICT sector have led the libraries to usedifferent ways of communicating with their users, especially with the emergenceof different social networks, with provision of opportunities and capabilities forlibraries, whether at the level of connection and communication with users, ormarketing them and their various services or providing services, such as: currentawareness service and reference service, which required libraries to developpolicies for using social networks. This study attempts to identify library policiesrelated to social networks, reviews and analyzes the policies presented in asample of foreign libraries, and finally, finally, it provides a model for a policysuitable for adoption and work through it in Arabic libraries.